Economic and social impacts of COVID-19 and public health measures: results from an anonymous online survey in Thailand, Malaysia, the UK, Italy and Slovenia. Issue 7 (20th July 2021) - Osterrieder, Anne; Cuman, Giulia; Pan-Ngum, Wirichada; Cheah, Phaik Kin; Cheah, Phee-Kheng; Peerawaranun, Pimnara; Silan, Margherita; Orazem, Miha; Perkovic, Ksenija; Groselj, Urh; Schneiders, Mira Leonie; Poomchaichote, Tassawan; et al.
Abstract : Objectives: To understand the impact of COVID-19 and public health measures on different social groups, we conducted a mixed-methods study in five countries ('SEBCOV—social, ethical and behavioural aspects of COVID-19'). Here, we report the results of the online survey. Study design and statistical analysis: Overall, 5058 respondents from Thailand, Malaysia, the UK, Italy and Slovenia completed the self-administered survey between May and June 2020. Poststratification weighting was applied, and associations between categorical variables assessed. Frequency counts and percentages were used to summarise categorical data. Associations between categorical variables were assessed using Pearson's χ 2 test. Data were analysed in Stata 15.0 Results: Among the five countries, Thai respondents reported having been most, and Slovenian respondents least, affected economically. The following factors were associated with greater negative economic impacts: being 18–24 years or 65 years or older; lower education levels; larger households; having children under 18 in the household and and having flexible/no income. Regarding social impact, respondents expressed most concern about their social life, physical health, mental health and well-being. There were large differences between countries in terms of voluntary behavioural change, and in compliance and agreement with COVID-19 restrictions. Overall, self-reported compliance was higher among respondents who self-reported a high understanding of COVID-19. UK respondents felt able to cope the longest and Thai respondents the shortest with only going out for essential needs or work. Many respondents reported seeing news perceived to be fake, the proportion varying between countries, with education level and self-reported levels of understanding of COVID-19. Conclusions: Our data showed that COVID-19 and public health measures have uneven economic and social impacts on people from different countries and social groups. Understanding the factors associated with these impacts can help to inform future public health interventions and mitigate their negative consequences. Trial registration number: TCTR20200401002.